Deteksi Kandungan Nitrit dan Hidrogen Peroksida dalam Produk Sarang Burung Walet Bersih Asal Indonesia - Siti Gusti Ningrum (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2021)
The objective was to investigate nitrite contents of edible bird’s nest product for human consumption. The investigated edible bird’s nest included 19 samples from multiple lots of commercially local products. Nitrite concentrations were determined by spectrophotometry. Nitrite was detected in low concentration (10.752±1.515 ppm). Detection of adulteration which is residue of hydrogen peroxide was conducted in the present study. Hydrogen peroxide was detected by rapid test which specific for hydrogen peroxide. From 19 sample tested, there was no residue of hydrogen peroxide contained in the products. These results provide new information for evaluating nitrite and hydrogen peroxide in local edible bird’s nest products regarding potential public health consequences.